Urolithiasis in a child with acute lymphoblastic leukemia - a case report and review of literature - Dr. Sangeetha Geminiganesan; Dr. Niranjana Varadaraju; Dr. Latha M Sneha; Dr. Julius Scott (Pediatric Review: International Journal of Pediatric Research, 2017)
3A two years old girlwith newly diagnosed acute lymphoblastic leukemia on induction chemotherapy developed abdominal colic and passage of powdery material in the urine. Ultrasound abdomen revealed stone in the right kidney. She was treated with adequate hydration and alkali therapy andimprovedsymptomatically. She has completed intensive phase of chemotherapyand had no recurrence of symptoms. Repeat ultrasound after two months of therapy showed no stones. Though renal stone disease is rare in childhood leukemia, it should be ruled out, as abdominal colic is generally attributed to the common side effects of drugs used in chemotherapy.